Monocytes as an early risk factor for acute graft-versus-host disease after allogeneic hematopoietic stem cell transplantation - Sun, Huimin; Wu, Linjie; Zhao, Xueying; Huo, Yingying; Dong, Peiyuan; Pang, Aiming; Zheng, Yawei; Han, Yiwen; Ma, Shihui; Jiang, Erlie; Dong, Fang; Cheng, Tao; et al. (Frontiers in Immunology, 2024)
Acute graft-versus-host disease (aGVHD) is a major complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and contributes to high morbidity and mortality. However, our current understanding of the development and progression of aGVHD after allo-HSCT remains limited. To identify the potential biomarkers for the prevention and treatment of aGVHD during the early hematopoietic reconstruction after transplantation, we meticulously performed a comparative analysis of single-cell RNA sequencing data from post-transplant patients with or without aGVHD. Prior to the onset of aGVHD, monocytes in the peripheral blood of patients with aGVHD experienced a dramatic rise and activation on day 21 post-transplantation. This phenomenon is closely aligned with clinical cohort results obtained from blood routine examinations. Furthermore, in vitro co-culture experiments showed that peripheral blood monocytes extracted from patients with aGVHD approximately 21 days post-transplantation induced a significantly higher proliferation rate of allogeneic T cells compared to those from patients without aGVHD. Our study indicates that monocytes could be a crucial early clinical risk factor for the development of aGVHD, and this insight could potentially guide the timing of monitoring efforts, recommending assessments at the pivotal juncture of approximately day 21 post-transplantation, shedding fresh light on the significance of early hematopoietic regeneration in relation to the onset of aGVHD.